Lucky broken girl - Behar, Ruth, 1956- (Nancy Paulsen Books, 2017)
In 1960s New York, fifth-grader Ruthie, a Cuban-Jewish immigrant, must rely on books, art, her family, and friends in her multicultural neighborhood when an accident puts her in a body cast.